Pertanggungjawaban Pidana terhadap Tindakan Aparat dalam Penanganan Unjuk Rasa Berdasarkan Konsep Command Responsibility di Indonesia - Permatasari, Era; Hafrida; Erwin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the criminal liability of law enforcement officers in handling public demonstrations based on the concept of command responsibility in Indonesia. Public demonstrations are constitutional rights guaranteed by laws and regulations. However, in practice, there are still actions by law enforcement officers that potentially violate the law and human rights during the security and dispersal of demonstrations. The main issue of this research is how criminal liability is regulated and how the concept of command responsibility can be applied to superiors who knew or should have known about violations committed by their subordinates. This research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that criminal liability may be imposed not only on direct perpetrators but also on commanding officers who had authority and control, provided that they knew or should have known about the violations and failed to take necessary measures to prevent or punish such acts. Therefore, the concept of command responsibility serves as an important mechanism for ensuring accountability among law enforcement officers and protecting human rights in the handling of public demonstrations in Indonesia.